2012
DOI: 10.4187/respcare.01485
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary Rehabilitation Enhances Heart Rate Recovery in Patients With COPD

Abstract: In subjects with COPD, exercise-based rehabilitation improves heart rate recovery, modestly though, which indicates a degree of attenuated autonomic dysfunction. Exercise and muscular oxidative capacity, as expressed by V(O(2))/t slope, is also improved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 63 publications
2
13
0
4
Order By: Relevance
“…This is likely due to certain drug administration as well as augmented sympathetic drive secondary to generalized neurohumoral activation and mechanical alteration of the chest cavity that is often evident in COPD (Georgiopoulou et al, 2012). In the present study the acceleration of heart rate kinetic response observed after pulmonary rehabilitation at the onset and recovery of constant-load exercise test (Table 3) provides evidence for physiologic improvement in cardiovascular function (Gimeno-Santos et al, 2014;Puente-Maestu et al, 2000).…”
Section: Discussionsupporting
confidence: 49%
“…This is likely due to certain drug administration as well as augmented sympathetic drive secondary to generalized neurohumoral activation and mechanical alteration of the chest cavity that is often evident in COPD (Georgiopoulou et al, 2012). In the present study the acceleration of heart rate kinetic response observed after pulmonary rehabilitation at the onset and recovery of constant-load exercise test (Table 3) provides evidence for physiologic improvement in cardiovascular function (Gimeno-Santos et al, 2014;Puente-Maestu et al, 2000).…”
Section: Discussionsupporting
confidence: 49%
“…Importantly, however, β-blockers could be beneficial on exacerbation because of other mechanism than reduction of heart rate, because we showed that heart rate had no significant effect on non-fatal pulmonary complications. In addition, exercise therapy might achieve a lower resting heart rate [28].…”
Section: Discussionmentioning
confidence: 99%
“…Recent data the researcher shows an imbalance in chronic obstructive pulmonary patients leads to an increased resting heart rate. 17 According to opinions Streuber et al, rehabilitation research beneficial effects on heart rate parameters in patients with heart failure. However, long term training programs to create significant changes in heart failure is needed that has been seen in sympathovagal patients.…”
Section: Discussionmentioning
confidence: 99%